Prospect for development of Open Access in Argentina - Miguel, Sandra (2012)
This perspective article presents an overview of the Open Access movement in Argentina, from a global and regional (Latin American) context. The article describes the evolution and current state of initiatives by examining two principal approaches to Open Access in Argentina: golden and green roads. The article will then turn its attention to: the support that Open Access receives from governmental sources; collaboration with international projects; and the perspective of Argentine authors regarding Open Access and self-archiving. It concludes with a reflection on the outlook, the main barriers and opportunities for Open Access in Argentina